(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
يلعب التمويل الزراعي دوراً هاماً في عملية التنمية الزراعية. من خلال توفير رؤوس الأموال للاستثمار في الزراعة. بهذا المعنى لا يمكن فصل مسألة التمويل عن إستراتيجية التنمية المراد تحقيقها. يهدف البحث إلى إلقاء الضوء على الواقع الراهن للتمويل الزراعي الحكومي في الأردن وسورية, وللكشف عن مدى كفاءته في مجال الإقراض والتحصيل واستقطاب المدخرات. في ضوء المؤشرات التي درسناها في هذا البحث, فقد تبين لنا, تراجع أداء المصرف الزراعي التعاوني في سورية في عام 2005 بالقياس إلى الأعوام السابقة. فقد تراجعت نسبة التمويل الذاتي إلى 11.26 بالمئة, وتراجعت أيضاً نسبة التوظيفات والتحصيلات, والكفاءة الإدارية, في حين زادت التكاليف التشغيلية. أما بالنسبة لمؤسسة الإقراض الزراعي في الأردن فقد زادت نسبة تمويلها الذاتي إلى 54.5 بالمئة من إجمالي مواردها في عام 2005 في حين كانت في عام 2001 لا تزيد عن 45.6 بالمئة. أما بقية المؤشرات فقد سجلت تراجعاً واضحاً, فقد تراجعت قيمة القروض وعددها وتراجعت التحصيلات, وزادت التكاليف التشغيلية. من الأسباب الرئيسة لتراجع كفاءة مؤسسات الإقراض الحكومي في الأردن وسورية التدخل الحكومي في عمل هاتين المؤسستين. Agricultural finance plays an important role in agriculture development by providing finance for investment in agriculture. We can not separate finance from the development strategy which should be achieved. This research emphasizes the status of government agricultural finance in Jordan and Syria and to see its efficacy on credit and repayment, snatching instance of saving. According to different aspects which studied in this research we found decreasing in performance of Agricultural Cooperative Bank in Syria in 2005 as comparing with the previous years. We noticed that there is decreasing in self finance by 11.26%. Also there is decreasing in repayment and management efficiency percent, on the other hand there was an increase in operating costs. In the Agricultural Credit Corporation in Jordan, there was an increase in self-resources which represented 54.4% from total resources in 2005. It was 45.6% in 2001; while there was a decrease in credit value and number of loans and repayment with increase in operating costs. We noticed that the government in both countries plays a role in the work and the institution policy of the Governmental Agricultural Finance in Jordan and Syria which lead to a reduction in the work efficacy for these institutions.